Flamenco in education: building European identity and social belonging - Jesus Heredia-Carroza; Carmen Lopez-Ruiz; Angeles Carrosa-Zayas; Carlos Chavarria-Ortiz (Eastern Journal of European Studies)
This paper deepens into the future teachers' outlooks on integrating flamenco in the educational context and its effects on the society. A group of 301 forms was carried out with university students enrolled in programmes related to education to assess the impact of incorporating flamenco into the educational syllabus. The results from this descriptive statistical assessment indicate that 88.4% of respondents were in favor of flamenco's inclusion. The participants of the form emphasized how flamenco has the potential to reinforce cultural identity, preserve heritage and promote relations between generations. The outcomes make certain that flamenco's inclusion into the syllabus enhances cohesion in the society and provides more support for belonging to the community. Flamenco is more than a cultural tradition as it is also a fundamental asset for Europe's legacy and time to come. Flamenco contributes to preserving and promoting Spain and Europe's cultural richness, safeguarding its role as a source of inspiration and growth for posterity, due to its promotion of belonging and encouragement of citizenship,